Children of mercury the lives of the painters - Bucklow, Spike (Reaktion Books, 2022)
Children of Mercury is a bold new account of the lives of pre-modern painters, viewed through the lens of The Seven Ages of Man, a widespread belief made famous in the 'All the world's a stage' speech in Shakespeare's As You Like It. Spike Bucklow follows artists' lives from infancy, through childhood, adolescence and adulthood, to maturity, old age and death. He tracks how lives unfolded for both male and female painters, from the famous, like Michelangelo, through Artemisia Gentileschi and Mary Beale to those who are now forgotten, like Jehan Gillemer. The book draws on historic biographies, artists' own writings and, uniquely, the physical evidence offered by their paintings
Keywords: Geschichte 1420-1800; Maler; Malerei; Vita; Painters / History; Art / History; Art, Renaissance; Peintres / Histoire; Art / Histoire; Art de la Renaissance; art history; Art; Painters; History